Signification politique du climat - Bernard Lamizet (Communication)
The notion of climate promotes a political view of space and time, one that evokes particular representations of history, memory, forecast and sustainable development. It also imposes a particular form of limitation on the powers that be, constrains political and media discourses, and conjures up the specter of violence. In this article, the author examines the various meanings of climate at the level of the unconscious.